Reducing Silica Levels in WTP PLTGU X Wastewater using Rice Husk Filter Membranes - Indah Agus Setiorini; Indah Pratiwi; Irawan Rusnadi; Amiliza Miarti; Achmad Faisal Faputri; Dian Kurnia Sari; Reco Rambang Putra Negsagis (Universitas PGRI Madiun, 2024)
During the water demineralization process, silica content is increased due to the failure of the chemical reagent. This shows the need to perform a blowdown action to reduce silica content in the water. Therefore, this research aimed to determine the effectiveness of silica reduction in the Water Treatment Plant (WTP) of PLTGU X by observing the permeate flux values relative to time and operating pressure variables, using ceramic membrane made from rice husk. To achieve the objective, ceramic membrane was made from rice husk additives, with a pore diameter of 365 nm and a surface area of 25 cm². The results showed that the composition ratio of clay, rice husk, and iron powder was 82.5%, 15%, and 2.5%, respectively. Furthermore, ceramic membrane with rice husk additives successfully reduced silica content from 1250 ppb to 890 ppb at a pressure of 1.5 bar and 90 minutes of operation and from 1250 ppb to 710 ppb at 2 bar and 90 minutes of operation. This suggested that wastewater could be processed again in the demineralization plant to produce demineralized water. The best membrane performance in the filtration process was achieved at 90 minutes with a pressure of 2 bar, which successfully reduced silica content by 43.2%, with a permeate flux of 3.44 L/m².